Kinetics of the nopol synthesis by the Prins reaction over tin impregnated MCM-41 catalyst (2013)
ABSTRACT: The kinetics of the nopol synthesis by Prins condensation of b-pinene and paraformaldehyde over Sn-MCM-41 synthesized by impregnation was evaluated using the initial reaction rate method. The reaction rate equation obtained from a kinetic model based on the Langmuir–Hinshelwood formalism with the surface reaction of adsorbed reactants on catalytic sites of the same nature as the limiting step, gave a good prediction of the experimental data. The effect of temperature on the kinetics of nopol synthesis over Sn-MCM-41 obtained by impregnation was studied between 75 and 100 °C. The robustness analysis of the kinetic model showed that the surface reaction constant, k0 sr , should be about 0.185 mol g-1 h-1 at 90 °C, while the ratio between the adsorption equilibrium constant of b-pinene, KA, and formaldehyde species, KB, is approximately 1.2:1 (KA:KB). The obtained apparent activation energy and pre-exponential factor are 78 kJ/mol and 2.3 * 1010 mol g-1 h-1, respectively, but compensation effect analysis using both experimental and simulated data gave strong evidence of the dependency in temperature of the apparent Arrhenius parameters.